Implementation Of Coretax In Improving Taxpayer Compliance In The Tax Administration System At Cv Kirana Cahaya Sejahtera - Temasona Putra Waruwu; Kurniawan Sarototonafo Zai; Maria Magdalena Bate'e (UNIVED Press, 2025)
Tax is a mandatory contribution to the state owed by individuals or bodies that is mandatory based on the Law, without receiving direct compensation and is used for state needs for the greatest prosperity of the people. The purpose of this study is to find out how Coretax is implemented in improving Taxpayer Compliance in the Tax Administration System at CV Kirana Cahaya Sejahtera. The type of study used is quantitative research, namely the method. The purpose of this study is to test existing theories, both to prove their truth and to reject the theory. The data used in this study are primary data and secondary data. Primary data is data obtained directly from the source or can be called primary data. The data collection techniques used are observation, interviews and documentation. The data analysis techniques used are data collection, data presentation, data reduction and conclusion drawing. From the results of the study, it was obtained that the application of the CoreTax system in the tax administration of CV. Kirana Cahaya Sejahtera was built on a comprehensive legal basis, which reflects the government's commitment to modernizing the national taxation system. This legal framework not only provides legitimacy for the implementation of CoreTax, but also regulates technical and operational aspects that guarantee the effectiveness and security of the system. The main basis for the implementation of CoreTax is based on the Law on General Provisions and Tax Procedures (UU KUP) which has undergone several changes to accommodate the development of information technology in tax administration. The DJP Coretax system is a step forward in the digitalization of taxation at CV. Kirana Cahaya Sejahtera, but still faces various challenges that need to be addressed immediately. With improved infrastructure, taxpayer education, and service optimization, it is hoped that this system can provide maximum benefits for all parties.